Pengaruh Motivasi Kerja, Komunikasi, dan Kompensasi Terhadap Kepuasan Kerja Pegawai Negeri Sipil (PNS) (Studi Empiris pada Kantor Pertanahan Kota Semarang) - Putri Iga Fatikhatun Nisa; Askar Yunianto (Universitas Batanghari, 2023)
The purpose of this research is to analyze the effect of work motivation, communication, and compensation on job satisfaction. The object of this research is the Semarang City Land Office. This study used a sample of 91 respondents where sampling was taken through purposive sampling. Data analysis in this research used multiple linear regression analysis with the SPSS 26 program. The results of the research are : (1) Work motivation has a positive and significant effect on job satisfaction of civil servants (PNS) at the Land Office of Semarang City. (2) Communication has a positive and significant effect on job satisfaction of civil servants (PNS) at the Land Office of Semarang City. (3) Compensation has a positive and insignificant effect on job satisfaction of civil servants (PNS) at the Land Office of Semarang City.